KENIKMATAN KERJA, DUKUNGAN ORGANISASI YANG DIPERCAYA TERHADAP KETERLIBATAN KARYAWAN: WORK ENJOYMENT, PERCEIVED ORGANIZATIONAL SUPPORT TOWARDS EMPLOYEE ENGAGEMENT - Fadhli, Muhammad; Hanifa, Fatin (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Introduction Employee engagement is how employees attach to work and the organization they are living in. Among those that can help in growing employee engagement is work enjoyment, namely how employees enjoy work. Then another factor is perceived organizational support, namely the support provided by the organization so that employees who work receive support in every job. Objective This study aims to determine the role of work enjoyment and perceived organizational support for employee engagement in employees. Method The quantitative survey approach used in this research involves as many as 171 employees through quota sampling. Collecting data used psychology scale that reflects the construct of each variable and then analyzed using multiple linear regression techniques. Result The results of this study indicated that perceived work enjoyment and organizational support play a role in employee engagement with a significance value of 0.000 (p <0.05). Conclusion Based on result, it showed that perceived work enjoyment and organizational support for employee engagement on employees. Keywords employee engagement, work enjoyment, perceived organizational support, employee. ABSTRAK Pendahuluan Employee engagement merupakan keterikatan karyawan terhadap pekerjaan dan organisasi yang dijalaninya. Diantara yang berperan dalam menumbuhkan employee engagement adalah work enjoyment yaitu situasi bagaimana karyawan menikmati pekerjaannya. Kemudian faktor lainnya adalah perceived organizational support yaitu dukungan yang diberikan organisasi agar karyawan yang bekerja mendapat dukungan dalam setiap pekerjaannya. Tujuan Penelitian ini bertujuan untuk mengetahui peran dari work enjoyment dan perceived organizational support terhadap employee engagement pada karyawan. Metode Pendekatan kuantitatif survey digunakan dalam penelitan ini dengan melibatkan sebanyak 171 orang karyawan melalui quota sampling. Pengambilan data menggunakan skala psikologi yang mencerminkan konstruk masing-masing variabel kemudian dianalisis menggunakan teknik regresi linear berganda. Hasil Berdasarkan temuan pada penelitian ini menunjukkan work enjoyment dan perceived organizational support berperan terhadap employee engagement pada karyawan dengan nilai signifikansi sebesar 0,00 (p<0,05). Kesimpulan: Hal tersebut menunjukkan bahwa work enjoyment dan perceived organizational support terhadap employee engagement pada karyawan. Kata Kunci: employee engagement, work enjoyment, perceived organizational support, karyawan